A Rare Complication of Transcatheter Aortic Valve Replacement: Delayed Down Migration of a Portico Valve - Busra GUVENDI SENGOR; Cemalettin YILMAZ; Regayip ZEHIR (Medeniyet Medical Journal)
There are some complications after transcatheter aortic valve replacement (TAVR), which is an alternative to surgery for the treatment of severe aortic stenosis. Valve migration, an unusual but life-threatening complication of TAVR, usually occurs during or several hours after the procedure and is associated with poor outcome. Therefore, operators must be experienced in rescue treatments. Placement of a second prosthesis as a salvage strategy appears to be a safe method to avoid the need for conversion to surgery.